Pengaruh ilmu ma’ani dalam perkembangan gaya bahasa dakwah masa kini - Hasanah, Nur Hidayatul; Shodiq, Jafar; Salsabilah, Sabrina Putri (Maliki Interdisciplinary Journal, 2025)
Ma'ani science, as one of the branches of Arabic rhetoric (balaghah), plays a significant role in the development of contemporary da'wah (Islamic preaching) language style. This study highlights the influence of ma'ani science on the success of da'wah communication, rhetorical skills, contextualization of messages, language aesthetics, and da'wah content development. In terms of communication, ma'ani science enables preachers (da'i) to select precise words and sentence structures, making religious messages clear and easily comprehensible to diverse audiences. The rhetorical skills acquired from ma'ani science help da'i in crafting persuasive and engaging sermons, thereby enhancing the effectiveness of da'wah. The contextualization of da'wah messages has become essential in the era of globalization, where messages must be tailored to the social, cultural, and linguistic conditions of the audience. Ma'ani science provides an in-depth understanding of how to deliver relevant and contextually appropriate messages. Additionally, the linguistic beauty taught in ma'ani science makes da'wah more captivating and emotionally resonant, with aesthetically pleasing and meaningful sentence structures. The development of da'wah content, supported by strong textual references from the Qur'an and Hadith, is also reinforced through ma'ani science, lending weight and authority to the conveyed messages.